Developing Students' 21st-Century Skills Through A Multidisciplinary Approach - Paskha Marini THANA; Tini ADIATMA; Ratu Bulkis RAMLI (RADINKA JAYA UTAMA PUBLISHER, 2022)
The 21st century is characterized by the rapid development of science, technology, and information. Along with the changes and advances that occur, 21st-century skills have emerged which are new needs to face the increasingly complex challenges of life. Life will not be able to be compartmentalized in one discipline alone, but rather run with a whole experience that uses various disciplines that combine with each other in solving a problem. Seeing these conditions, education has the biggest contribution in preparing a generation that has 21st-century skills that are ready to compete globally. One of the ways is to use a multidisciplinary approach by integrating interdisciplinary learning which is usually still compartmentalized so that they form a connection with the aim of providing a deep understanding along with the development of 21st-century skills of students. This research is a literature study that will describe how learning activities using a multidisciplinary approach can have an influence on developing students' 21st-century skills.